Use of Adeno‐Associated and Herpes Simplex Viral Vectors for In Vivo Neuronal Expression in Mice. Issue 1 (1st October 2015) - Penrod, Rachel D.; Wells, Audrey M.; Carlezon, William A.; Cowan, Christopher W.
Abstract: Adeno‐associated viruses and the herpes simplex virus are the two most widely used vectors for the in vivo expression of exogenous genes. Advances in the development of these vectors have enabled remarkable temporal and spatial control of gene expression. This unit provides methods for storing, delivering, and verifying expression of adeno‐associated and herpes simplex viruses in the adult mouse brain. It also describes important considerations for experiments using in vivo expression of these viral vectors, including serotype and promoter selection, as well as timing of expression. Additional protocols are provided that describe methods for preliminary experiments to determine the appropriate conditions for in vivo delivery. © 2015 by John Wiley & Sons, Inc.